The archaeology of Amboseli: ceramics, lithics, and special finds recovered during 2015 surveys and excavations in Olgulului/Olarashi Group Ranch, Kenya - Shoemaker, Anna (Uppsala University, 2018)
This data was acquired during the production of a PhD thesis pertaining to the archaeology of Amboseli. The amount of information obtained during ceramic and lithic analysis was often in excess of the immediate aims of this research project. This level of detail was recorded to build a robust dataset that will allow different questions to be asked of the data in the future. To facilitate ongoing analysis, supplementary data relating to the attributes and location of the lithics, ceramics, and special finds encountered during surveys and excavations has been made available here. See README-file for description of content of each datafile.

The dataset was originally published in DiVA and moved to SND in 2024.

Dessa data samlades in under arbetet med en doktorsavhandling om arkeologin i Amboseli. Se engelsk version av denna katalogpost samt README-fil för ytterligare information om data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
The archaeology of Amboseli: ceramics, lithics, and special finds recovered during 2015 surveys and excavations in Olgulului/Olarashi Group Ranch, Kenya
Keywords: Archaeology; Arkeologi; Archaeology; Arkeologi; Artefact; Artefact